Happiness Elements of Elders in Rural Northeast, Thailand: Dynamic of Social Change in Globalization Era - Rukchanok Chumnanmak; Dusadee Ayuwat; Wanichcha Narongchai (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to study elements for the elder's happiness in rural area of the north- eastern region, under the dynamic of social changes in the globalization. The study is a qualitative research having the unit of analysis both of individual and community lev- els. Data is collected from the in-depth interview with 18 elders, covering all age ranges, living in rural areas. The studiedarea is named O-lo village in PhuKiew district, Chaiya- phum province where contains high rates of the elders in the northeast. The data was collected during June to October 2017 using interview guide as a tool, and is analyzed with content analysis. The result reveals that the elders in O-lo community are happy with their family conditions. Their happiness consists of 4 elements as the followings. The first element is family meaning there are families or relatives to take care of. The elder always ask in order to follow up for their offspring's well-being and give moral support to them. The second element is regarding their health. The elders are in good health and able to take care of themselves. They can also help out their families with housework. This is also the result of their convenient accessibility to medical treatment. The third element is economic aspect. The elders have their occupations and incomes from various sources including their work, money given from their children, and the welfare elder allowances. The last element is social aspect. They feel safety in their lifes and properties. Moreover, they join social activities organized by the community in order to relieve themselves from stress, make merit in temples, and participate in any activities enhancing value of the elders.